THE IMPLEMENTATION OF STUDENT MANAGEMENT IN ELEMENTARY SCHOOL: A REFLECTION FROM SD NEGERI 2 BEBENGAN - Purdiyanti; Titik Haryati; Ghufron Abdullah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the implementation of student management at SD Negeri 2 Bebengan, a Transformative Model School in Boja District, Kendal Regency. The research aims to describe how key components of student management—planning, development, evaluation, and transfer—are practiced and contribute to improving educational quality. Using a qualitative descriptive method, data were collected through structured observations, semi-structured interviews, and documentation. The findings show that student planning is conducted collaboratively through data-informed strategies involving recruitment, orientation, and placement. Student development is supported through mentoring, guidance, co-curricular activities, and character education, ensuring holistic growth. Evaluation of learning is systematic, combining diagnostic, formative, and summative assessments used to adapt instructional practices and inform academic decisions. The school also employs regulated transfer and dropout management procedures to maintain continuity in student learning. These practices are aligned with national education standards and international best practices in student-centered management. The study concludes that structured and inclusive student management enhances academic outcomes and personal development. Recommendations include improving digital data systems, enhancing teacher training in socio-emotional learning, and strengthening parental involvement and post-pandemic support systems.